Lalbagh rethought exploring the incomplete Mughal fortress in Dhaka, Bangladesh - Rashid, Md. Mizanur (2011)

(untitled)
Lalbagh Fort is probably the most ambitious building activity undertaken by the Mughal rulers of Dhaka. Although the complex coined the name ‘Lalbagh Fort’ because of its huge fortification walls and gateways, the master plan and the layouts of the buildings that still exist suggest little or no similarity with the other Mughal forts either in Bengal or any other parts of India. The construction of the complex ran only for one decade and it was left abandoned for unknown reason. The brief history of the megaproject had been buried since 1688 and the fort remained incomplete till date. Several attempts have been made so far to recover the memories of this monument after the amnesia of centuries. However, the incomplete nature of construction, the limited amount of archaeological resource, literary evidences and epigraphic records at the disposal of the architectural historians appears as the main thicket. Filling up this lacuna using these apparently inconspicuous resources certainly put the existing discourse regarding this monument in a perplexed situation. This perplexity is the character of the architecture of Lalbagh today. It poses a long list of questions regarding its original master plan, its purpose and its history of construction, of which we are yet to provide definite answers being in a telescopic distance. This paper is an attempt to examine and compare different contesting hypothesis regarding its architecture. The main idea is to explore the building by drawing parallels with other Mughal buildings in Bengal and outside. It would provide us further room to rethink and reinterpret all the possibilities and posit a narrative of its architecture as it was originally planned and designed.